Violence, hospitality, and the cross : reappropriating the atonement tradition - Boersma, Hans, 1961- (Grand Rapids, Mich. : Baker Academic, 2004)
"In this study, Hans Boersma proposes an understanding of the atonement that is sensitive to both the Christian tradition and postmodern critiques of that tradition."--BOOK JACKET.
PART 1. The divine face of hospitality. 1. The possibility of hospitality -- 2. Limited hospitality : election and violence in eternity -- 3. Preferential hospitality : election and violence in history -- PART 2. The cruciform face of hospitality. 4. Atonement, metaphors, and models -- 5. Modeling hospitality : atonement as moral influence -- 6. Atonement and mimetic violence -- 7. Hospitality, punishment, and the atonement -- 8. Atonement, violence, and victory -- PART 3. The public face of hospitality. 9. The church as the community of hospitality -- 10. Public justice and the hospitality of liberation -- Epilogue. The end of violence : eschatology and deification.
Includes bibliographical references (p. 263-275) and indexes.
Keywords: Atonement; Hospitality -- Religious aspects -- Christianity; Violence -- Religious aspects -- Christianity